Cost Of Illness COVID-19 Inpatient Installation at the UGM Academic Hospital - Hutahaean, Amsaline Vingky; Andayani, Tri Murti; Widayanti, Anna Wahyuni (Majalah Farmaseutik, 2024)
COVID-19 has become a worldwide pandemic, especially in Indonesia. The high number of COVID-19 cases in Indonesia has a financial impact, as the government must shoulder the cost of dealing with it. The study aimed to determine the direct cost and total cost (cost of illness) of COVID-19 patients at RSA UGM Yogyakarta from a hospital perspective, as well as the differences in total direct cost of hospitalized COVID-19 patients based on age, gender, length of stay, severity, and comorbidity. The cross-sectional study design of the analytic observational research method is based on a hospital perspective. Data was collected retrospectively from the patient's medical record, detailed healthcare expenditure data, and patient claim files. The data was analyzed using univariate, bivariate, and multivariate methods. The study's findings requested the number of inpatient COVID-19 patients as many as 104 samples that satisfied the inclusion specifications, as well as the total direct medical costs of Rp. 2.346.150.137 with an average cost of Rp. 22.559.154 for each patient. The most expensive components were pharmaceutical and BMHP prices of Rp. 958.410.599 (40.85%) and medical support costs of Rp. 725.163.700 (30.91%). Age, length of stay, severity of comorbidities, and usage of antivirals all have an impact on direct medical costs.Keywords: COVID-19, hospital costs, hospital perspective, hospitalization